2020
DOI: 10.1186/s40337-020-00302-7
|View full text |Cite
|
Sign up to set email alerts
|

The Portuguese version of the body investment scale: psychometric properties and relationships with disordered eating and emotion dysregulation

Abstract: Background: This study aimed to examine the psychometric properties of the Portuguese version of the Body Investment Scale (BIS) in a nonclinical sample of students and a clinical sample of outpatients with eating disorders, to analyse the differences in the BIS factors between the samples and to explore the relationships among body investment, eating disorder symptoms and difficulties in emotion regulation. Methods: The clinical (n = 93) and nonclinical (n = 448) samples completed self-report measures. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(67 reference statements)
2
6
0
1
Order By: Relevance
“…However, our findings are in line with previous literature suggesting that the pathway from self-esteem to binge eating is mediated by body image concerns [ 14 ]. However, the data also corroborate previous studies suggesting that negative feelings about the body and lower levels of self-protection are associated with disordered eating behaviors [ 41 ]. More specifically, the current study provides the first empirical evidence that body disinvestment acts as a mediator in the relationship between self-esteem and binge eating among both males and females.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our findings are in line with previous literature suggesting that the pathway from self-esteem to binge eating is mediated by body image concerns [ 14 ]. However, the data also corroborate previous studies suggesting that negative feelings about the body and lower levels of self-protection are associated with disordered eating behaviors [ 41 ]. More specifically, the current study provides the first empirical evidence that body disinvestment acts as a mediator in the relationship between self-esteem and binge eating among both males and females.…”
Section: Discussionsupporting
confidence: 90%
“…However, a recent study has demonstrated that such investment was negatively associated with ED symptoms. Specifically, negative feelings and attitudes towards the body, discomfort with physical touch and low levels of body protection significantly predicted a higher severity of disordered eating behaviors [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…BIS is a 24-item self-report [ 24 ], widely translated and diffusely used in scientific literature [ 40 , 41 ]. The scale is used in this paper in a self-made Italian translation due to the lack of an official version validated in this country.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it does appear that the items on this particular scale tap into a useful construct, especially for making broad discriminations between suicidal and non-suicidal adolescents [2]. Furthermore, this subscale has demonstrated stable external validity and is the dimension with the highest reliability in the English, Portuguese, and Spanish versions [2,9,11]. The I-BIS has been utilized to explore the association between body image and eating disorder symptomatology in adolescents [13] and female athletes [29], the level of physical activity achieved among male and female adolescents [15], the probability of following a diet to lose weight [30], and to analyze its role as a mediator between patients with diabetic foot ulcers and their quality of life [12].…”
Section: Introductionmentioning
confidence: 95%
“…To measure this construct, Orbach and Mikulincer [1] developed the Body Investment Scale (BIS), which is composed of four subscales, including body image feelings and attitude Psych 2024, 6 346 and body care (simplified as body image), body touch, body care, and body protection. However, this seminal work used an orthogonal rotation and a factorial structure, which has only been partially supported in posterior validation studies [2] and adaptations to other languages, such as Portuguese [9,10] or Spanish [11], where the factors were altered and correlated (oblique rotation), and some items covaried in models with the best fit. Moreover, other empirical studies used modified versions of the instrument with different structures of the subscales [8,12], whereas others have adapted the instrument to different languages based on their own translation-back-translation process [13][14][15] without exploring any psychometric properties of the adaptation.…”
Section: Introductionmentioning
confidence: 99%